If entrepreneurs ran the church : new visions for an old church - Kerridge, Peter (Society for Promoting Christian Knowledge, 2017)
Interviews with eight Christian entrepreneurs regarding how they would run the Church in the U.K.
Keywords: církev -- organizace a řízení; církev -- Velká Británie; podnikání -- Velká Británie; management -- Velká Británie; podnikatelé -- Velká Británie; podnikatelky -- Velká Británie; church -- organization and management; church -- Great Britain; business -- Great Britain; management -- Great Britain; businessmen -- Great Britain; businesswomen -- Great Britain; rozhovory; interviews